Inovasi Pengompresan Payudara pada Ibu Nifas dengan Menggunakan Daun Kol - Darmawati, Getrudis Askalian; Nanan, Greistiani; Hermafino, Fridolin; Wiwe, Grasela Kurniati; Mamo, Fransika Floriani; Navan, Gaudensia Astuti; Genjung, Fridolin Laurensia; Bela, Gerardis Fladiana Sarni; Deria, Helena (Pakis Journal Institute, 2025)
Breastfeeding is a natural process for a woman and has many benefits for both mother and baby. One of the problems that often arise during the postpartum period, or lactation period, is breast engorgement, also known as breast milk engorgement. This engorgement occurs due to the accumulation of milk caused by narrowing of the lactiferous ducts or because the mammary glands are not completely emptied. If not treated properly, breast engorgement can lead to more serious problems such as mastitis and breast abscesses. To increase the knowledge of postpartum mothers in preventing breast swelling. The method used in this community service is literature review and use of video. From community service aimed at postpartum mothers, there is an increase in knowledge regarding the dangers of breast swelling in postpartum mothers.